The Implementation of the Apostle Paul’s Exhortation on Living in Love Based on Romans 12:9–21 for Youth at Sungai Yordan Church, Nanga Pinoh - Rikus; Paulus Sentot Purwoko; Hendrikus (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
This study aims to analyse the extent to which the apostle Paul's exhortation on living in love, as written in Romans 12:9–21, is implemented among the youth of the Sungai Yordan Church, Jemaat Segala Bangsa, Nanga Pinoh, Melawi, West Kalimantan. A life rooted in love is reflected through doing good and serving others. Although the majority of the youth demonstrate growth in love through caring attitudes and mutual assistance, interview findings reveal the presence of behaviours contrary to the values of love, such as theft, harbouring resentment, conflict, and bullying. These indicate the need for continuous teaching on the principles of love. This research employs a quantitative approach, with data collected using a Likert scale and analysed through SPSS 25. Validity, reliability, and normality tests were conducted, along with hypothesis testing using the Confidence Interval formula and regression significance test (F reg) at a 5% significance level. The results show that the implementation of Paul's exhortation is categorised as high, with a Confidence Interval ranging from 129.6831 to 133.4955. The most dominant dimension in the implementation of love is "Serving Others" (D2), contributing 91.9%, while the dimension of "Doing Good" (D1) contributes 85.2%. These findings underscore the importance of reinforcing the values of service and kindness in the spiritual development of the church’s youth.